Answer:
f(x) will not have any roots.
Solution:
The roots of f(x) means the solution of f(x) = 0 which are the points where the function f(x) crosses the x axis. As the given equation, the highest power is 3, hence the equation will have total 3 roots.
Let us assume the three roots are a, b, c
Hence,
![x^(3)+2 x^(2)+3 x+4=(x-a)(x-b)(x-c)=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/35tgodqy8bqld7q1uon5e41wi49qazmb40.png)
Multiplying the brackets we get
![a* b* c =4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/806agzbz05nq566pvdl0xukoip1kz345qc.png)
So a, b, c must be the factors of 4
The possibilities of factors of 4 are +1, -1, +2, -2, +4, -4
Substituting the values we get,
![f(1)=1^(3)+2 * 1^(2)+3 * 1+4=10](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xnerlp8hgucfxp0ss8gvxyqody1hahs94j.png)
![f(-1)=\left(-1^(3)\right)+2 *(-1)^(2)+3 *(-1)+4=-1+2-3+4=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lffcw4it7nmts66oxt1pg3wtkpv0degxaw.png)
![f(2)=2^(3)+2 * 2^(2)+3 * 2+4=26](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q9jvr03vo8s7ncw6oc3qg8553hrbknrtxb.png)
![f(-2)=\left(-2^(3)\right)+2 *(-2)^(2)+3 *(-2)+4=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/87e44al62h1o24evu34gub57pctajgw4xv.png)
![f(4)=4^(3)+2 * 4^(2)+3 * 4+4=112](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wlycv2pqpw6l3vzu70g1ai0vaa0u6pj82d.png)
![f(-4)=-4^(3)+2 *(-4)^(2)+3 *(-4)+4=-40](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zm10aiy7786fkbdng0tow7vzooltuvtc91.png)
So, there are no values that satisfy the equation.
Hence f(x) will not have any roots.